ISLAM INDONESIA: DISKURSUS ISLAM POLITIK VIS-A-VIS ISLAM KULTURAL DARI PRA-KEMERDEKAAN HINGGA ERA REFORMASI - Adi Fadilah (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This paper deals with Islam in Indonesia through two great discourses: Political Islam and Cultural Islam. I try to explore the history and tranformation of both by library research from before independence until after New Order called reformation era. By using descriptive-analyses method, this paper concludes that the dynamic of the two poles was going on and also being actual around the society. The group of Political Islam with its vote through Islamic Parties wants to make Islam as an ideological principle and Indonesia as a religious country. Meanwhile, the group of Cultural Islam with the spirit of d’awa which want to realize Islam as the diffused values of live with the culture and also anti-sectarianism rejects the concept of Political Islam.